Beispiel Nr: 09
$ \text{Gegeben:}\\\text{Umfang} \qquad U \qquad [m] \\ \text{Länge} \qquad a \qquad [m] \\ \\ \text{Gesucht:} \\\text{Breite} \qquad b \qquad [m] \\ \\ b = \frac{U - 2\cdot a}{ 2}\\ \textbf{Gegeben:} \\ U=110m \qquad a=6m \qquad \\ \\ \textbf{Rechnung:} \\ b = \frac{U - 2\cdot a}{ 2} \\ U=110m\\ a=6m\\ b = \frac{110m - 2\cdot 6m}{ 2}\\\\b=49m \\ \small \begin{array}{|l|} \hline a=\\ \hline 6 m \\ \hline 60 dm \\ \hline 600 cm \\ \hline 6\cdot 10^{3} mm \\ \hline 6\cdot 10^{6} \mu m \\ \hline 0,006 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline U=\\ \hline 110 m \\ \hline 1,1\cdot 10^{3} dm \\ \hline 1,1\cdot 10^{4} cm \\ \hline 1,1\cdot 10^{5} mm \\ \hline 1,1\cdot 10^{8} \mu m \\ \hline 0,11 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline b=\\ \hline 49 m \\ \hline 490 dm \\ \hline 4,9\cdot 10^{3} cm \\ \hline 4,9\cdot 10^{4} mm \\ \hline 4,9\cdot 10^{7} \mu m \\ \hline 0,049 km \\ \hline \end{array}\\$